2008
DOI: 10.1167/iovs.08-1831
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Vision Rescue by Human Neural Progenitors in a Rat Model of Photoreceptor Degeneration

Abstract: Purpose As a follow-up to previous studies showing that human cortical neural progenitor cells (hNPCctx) can sustain vision for at least 70 days after injection into the subretinal space of Royal College of Surgeons (RCS) rats, the authors examined how functional rescue is preserved over long periods and how this relates to retinal integrity and donor cell survival. Methods Pigmented dystrophic RCS rats (n = 15) received unilateral subretinal injections of hNPCctx at postnatal day (P) 21; control rats (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 22 publications
(29 reference statements)
7
113
0
Order By: Relevance
“…Thus, hESCs are expected to substitute for the human fetus, at least in part, to unravel the mystery of human-specific developmental mechanisms (Cauffman et al, 2006(Cauffman et al, , 2009Choudhary et al, 2007;Dvash et al, 2004Dvash et al, , 2006Gjerstorff et al, 2008;Pera and Trounson, 2004;Rugg-Gunn et al, 2005). Even restricted to the ocular cells or tissues, only cultured cornea cell sheets induced from epithelial stem cells have been used for therapy (Nozaki et al, 2008;Sekiyama et al, 2006), and many induced cell types including those of retina and retinal pigmented epithelium have been used only in animal models (Kubota et al, 2006;MacLaren et al, 2006;Wang et al, 2008). Still, ocular cells good for therapeutic use may possibly be prepared from ES cells or iPS cells; however, the complex layered structure of the retina would be hard to regenerate as a tissue in present culture systems.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hESCs are expected to substitute for the human fetus, at least in part, to unravel the mystery of human-specific developmental mechanisms (Cauffman et al, 2006(Cauffman et al, , 2009Choudhary et al, 2007;Dvash et al, 2004Dvash et al, , 2006Gjerstorff et al, 2008;Pera and Trounson, 2004;Rugg-Gunn et al, 2005). Even restricted to the ocular cells or tissues, only cultured cornea cell sheets induced from epithelial stem cells have been used for therapy (Nozaki et al, 2008;Sekiyama et al, 2006), and many induced cell types including those of retina and retinal pigmented epithelium have been used only in animal models (Kubota et al, 2006;MacLaren et al, 2006;Wang et al, 2008). Still, ocular cells good for therapeutic use may possibly be prepared from ES cells or iPS cells; however, the complex layered structure of the retina would be hard to regenerate as a tissue in present culture systems.…”
Section: Discussionmentioning
confidence: 99%
“…As with RPCs, integration increases when NSCs are transplanted into young or injured host retina [43,44], and at the other extreme, NSCs transplanted into healthy adult monkey show little migration or integration, forming a monolayer of stable NSCs [45]. Integration may not be necessary to rescue photoreceptor cell loss; however, NSCs derived from committed CNS tissue rescue photoreceptor cells in animal models of retinal disease presumably by release of growth factors and/or phagocytosis of photoreceptor cell outer segments shed during the early steps of vision [46,47].…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…We have shown that a single subretinal injection of hNPC ctx leads to their migration and long-term engraftment in the subretinal space, as well as preserves vision in Royal College of Surgeons (RCS) rats, a wellestablished animal model for retinal degeneration. 20,21 This ability to survive in the subretinal space and offer neuroprotection is a powerful feature of these cells in treating retinal degenerative diseases. In addition, their ability to migrate long distances after subretinal injection permits the injection site to be targeted at the transient zone to avoid damaging macular vision that is already fragile from degeneration.…”
Section: Introductionmentioning
confidence: 99%